Monitoring whooping crane abundance using aerial surveys: Influences on detectability. (19th November 2013) - Strobel, Bradley N.; Butler, Matthew J.
ABSTRACT The whooping crane (Grus americana), an endangered species, has been counted on its winter grounds in Texas, USA, since 1950 using fixed‐wing aircraft. Many shortcomings of the traditional survey technique have been identified, calling into question its efficacy, defensibility, repeatability, and usefulness into the future. To improve and standardize monitoring effort, we began investigating new survey techniques. Here we focus on efficacy of line transect‐based distance sampling during aerial surveys. We conducted a preliminary test of distance sampling during winter 2010–2011 while flying the traditional survey, which indicated that detectability within 500 m of transects was 0.558 (SE = 0.031). We then used an experimental decoy survey to evaluate impacts of observer experience, sun position, distance from transect, and group size on detectability. Our results indicated decoy detectability increased with group size and exhibited a quadratic relationship with distance likely due to pontoons on the aircraft. We found that detectability was 2.704 times greater when the sun was overhead and 3.912 times greater when the sun was at the observer's back than when it was in the observer's eyes. We found that an inexperienced observer misclassified non‐target objects more often than an experienced observer. During the decoy experiment we used marks on the struts to categorize distances into intervals, but we found that observers misclassified distances 46.7% of the time (95% CI = 37.0–56.6%). Also, we found that detectability of individuals within detected groups was affected by group size and distance from transect. We discuss how these results inform design and implementation of future whooping crane monitoring efforts. Published 2013. This article is a U.S. Government work and is in the public domain in the USA.